Pedagogia da alternância na Escola Família Agrícola da Perimetral Norte: a inserção da educação ambiental para o desenvolvimento local - (:unkn) unknown (Brasil, 2021)
The present study aimed to verify the contributions of the Agricultural Family School of Perimetral Norte-EFAPEN, located in the municipality of Pedra Branca do Amaparí, a puppy community on the shore of Rod. Perimetral Norte, BR 210, KM 167 in the State of Amapá. School education unit with elementary and high school level. Under study, enabling the possibility to implement the Technical course in Agroecology together with its methodology, the Pedagogy of Alternation, in the integral formation of its students and in the rise of local development, with everything, the Insertion of Environmental Education in the context of teaching and learning of the man in the field to achieve sustainable development in school and in the community. E bring some considerations about Brazilian education, field education and environmental education in the context of development aiming to create in the field man a critical awareness of his rights as a citizen and of his duties as a production agent, including in this country man a concern with the care of agricultural practices, aiming at an economically virale and ecologically sustainable production that allows him to lie in the field and the field in harmony with biodiversity. The Maine objective of the research was to show the importance of the Téo aspects pressentem, which in any case, always be present in the life of the family school tumente. There was also interest in knowing the trajectory of the object of study, since it has been established for three decades (1991 to 2021) in the State of Amapá. For a study with objects of such diverse realities, The methodology used was the multiple case study method, because for the understanding of the object, there was a need for discussions on various areas of knowledge from a diverse literature for a dialectical understanding of the observes object. At the heart of the techniques, interviews, oral history, study plan, documentary research, bibliographic research, field research and observation were used. After data collection, a descriptive statistic was performed with a qualitative and quantitative approach. With the conclusion of the por it was noticed that EFAPEN contributes, in an incipient way with the environment, to the integral formation of its students and promotion of Social Capital through the Bond of solidarity, trust and cooperation, characteristics existing in the institution that uses the Pedagogy of Alternation. However, due to the numerous problems pointed out during its development, the results achieved by EFAPEN, for providing a basic education in the training of its regular students, are not sufficient for the formation of networks between partner institutions and, truz, to endure local development. Citizen participation in the development of sustainable alternatives, which put into practice learning and dialogue between generations, culture and different habits, allows establishing a common goal, which favos the elaboration of action plans in favor of nature and man, since these cannot dissociate. Finally, to consent to the formation of critical awareness, and thus encourei the participation of a population that knows how to exercise social and environmental rights and duties.
Keywords: Educação ambiental; Educação ambiental - ensino fundamental e médio; CNPQ::CIENCIAS HUMANAS::EDUCACAO